Species diversity, biological spectrum and phenological behavior of vegetation of a Muslim sacred grove in Southwest Bengal, India - Dr. Uday Kumar Sen Uday; RAM KUMAR BHAKAT (Smujo International, 2021)
Abstract. Sen UK, Bhakat RK. 2021. Species diversity, biological spectrum and phenological behavior of vegetation of a Muslim sacred grove in Southwest Bengal, India. Nusantara Bioscience 13: 219-231. Sacred groves are an age-old and worldwide phenomenon. They are traditionally made up of forest or surrounding forest zones that local people safeguard based on their spiritual relationship with the deities or ancestral spirits believed to reside in them. Social practices play a crucial role in conserving the environment and biodiversity. This research aimed to examine the current flora of a sacred grove's plant resources, biological spectrum, leaf size spectra, conservation status, and management of the Faringdanga Pir Babar Asthana in the Paschim Medinipur District of West Bengal in India. The floristic element of the study area revealed that the vegetation was diverse and composed of 162 species belonging to 148 genera over 51 families under 26 orders according to the Angiosperm Phylogeny Group (APG) IV classification. Because the study area is a sacred grove, it is relatively undisturbed, and traditional beliefs ensure that germplasm in the grove is protected. The current study could serve as a model for phytoclimatic research in India's sacred forests.